Vegetation history and environment changes since MIS 5 recorded by pollen assemblages in sediments from the western Bohai Sea, Northern China. (January 2020) - Li, Jie; Yang, Shixiong; Li, Rihui; Shu, Junwu; Chen, Xiaohui; Meng, Yuanku; Ye, Siyuan; He, Lei
Graphical abstract: Comprehensive diagram of percentages among trees, conifers, broadleaved trees, herbs and ferns, total pollen concentration, and mean grain size and sedimentary facies and units (the purple belts represent relatively sea level highstand periods). Highlights: Pinus and Quercus generally prevailed in the interglacial stage. Abundant herbs coincided with sandy sediments input in the interstadial periods. Fluctuations of AP and NAP revealed the sea level and climate changes. Abstract: Due to the lack of well-constrained chronology, the history of climate and vegetation associated with sea level changes during the late Quaternary has been poorly understood in the Bohai sea area. In this study, the upper 56.0 m-long sediment of the TJC-1 core in the western Bohai Sea was investigated using pollen and spore analyses, together with OSL, AMS 14 C dating, grain size, and foraminifera data. The chronologically well -constrained core records show that varying pollen and spore assemblages reflect changes in vegetation on the adjacent land, climate and sediment settings since MIS 5 stage. Arboreal pollen dominated by Pinus and Quercus generally prevailed during the warm periods (MIS 5a, 5c, 5e, MIS 3 and MIS 1), corresponding to the sea level highstands, while dominance of terrestrial herbs such as Artemisia and Chenopodiaceae indicate presence of grasslands during cold periods such as MIS 4, MIS 5b and 5d when sea level dropped significantly. During the stadial periods such as MIS 5b and MIS 5d, herbaceous assemblages predominated in relatively cold conditions, in response to fluvial and coastal high energy sedimentary environments. The dominance of herbs especially Chenopodiaceae in the early-middle of MIS 5 and early Holocene was probably associated with huge amounts of sandy sediments input from the Yellow River caused by strong rainfall. Furthermore, pollen concentration is closely related to sediment grain size, arboreal pollen and fern spores are especially deposited in the fine sediment while herbaceous pollen dominates in coarser sediment.